A Population Study of Health Status Among Sexual Minority Older Adults in Select U.S. Geographic Regions. (June 2019) - Dai, Hongying; Meyer, Ilan H.
Objective . This study seeks to examine the health disparities of sexual minority older adults. Method . We used a probability sample of adults older than 50 years in select U.S. regions from the 2014, 2015, and 2016 Behavioral Risk Factor Surveillance System with administration of the sexual orientation question ( n = 350, 778). Binary and multinomial logistic regression models were performed to examine health disparities in general health conditions, lifetime chronic health conditions, limitations in activities, substance use, access to care and preventive health behaviors by sexual minority status (straight, gay/lesbian, bisexual, other, and nonresponse), stratified by sex (male vs. female) and age group (50-64 vs. 65+ years). Results . Compared with their straight peers, sexual minority older adults had disparities in some health outcomes, including a higher prevalence of depressive disorder and substance use. However, the disparities were not uniform across gender and age groups. Both men and women sexual minorities had some advantages as well, related to preventive health behaviors (e.g., HIV testing), as compared with their straight peers. Nonrespondents in sexual orientation generally had better health outcomes than their straight peers. Conclusions . This study identifies health disparities among subgroups of lesbians, gay men, and bisexuals older adults and highlights the need to assess variability related to gender, sexual identity, and age of this high-risk population.